Measurement of total electron content (TEC) using virtual reference station (VRS) data at ionosphere layer / Norsuzila Ya'acob ... [et al.] - Ya'acon, Norsuzila; Yusof, Azita Laily; Ali, Mohd Tarmizi; Idris, Azlina (INSInet Publication, 2012)
This research presents the TEC value using levelling process based on time of the day, ionosphere height and location of the receivers in Malaysia. These 3 parameters will be used for project approach. The main focus is to study the concept of VRS techniques in Malaysia and the development of TEC calculation in ionospheric area using RINEX (Receiver Independent Exchange) VRS data format which received from JUPEM (Department of Survey and Mapping Malaysia) Kuala Lumpur. The target is to implement levelling process and calculation VRS total electron content and apply the dual frequency method in mapping functions, single layer model (SLM) and modified single layer model (M-SLM) for Total Electron Content (TEC). The results show that the content of TEC in Malaysia VRS station varies between -14.7006 TECU to maximum -33.9636 TECU. The vertical TEC values are precise, accurate and without multipath, unless the multipath environment is really terrible.